Membentuk Keluarga Sakinah, Mawaddah, Warahmah bagi Pasangan Suami Isteri Tuna Wicara Perspektif Hukum Islam - Triyono, Very; Fadila, Rahma (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. Forming a Sakinah, Mawaddah, Warahmah Family for a Spouse of a Speech Impaired Husband and Wife in the Perspective of Islamic Law (Study in Rebang Tangkas District, Way Kanan Regency) based on the results of pre-research to form a sakinah, mawaddah, warahmah family for a married couple with a speech impairment experiences several problems and challenges that are faced differently from other families in general, it does not even rule out the possibility in an effort to form a sakinah, mawaddah, warahmah family in a family of people with speech impairment is very complicated considering the imperfect physical condition that requires great effort and effort, because it has deficiencies. Aim. Based on the above background, the author formulates the main problem, namely, How does a married couple with a speech impairment form a sakinah, mawaddah, warahmah family from the perspective of Islamic law. Methods. This type of research is field research which is a case study located in Rebang Tangkas District. This field research was conducted on a married couple with speech impairment. Data obtained through several methods, namely, observation interviews and documentation, data analysis techniques are carried out through the stages of data collection, data reduction, and data presentation, then analysing using descriptive qualitative analysis methods. Results. The results of research on 4 speech impaired couples in Rebang Tangkas Subdistrict about forming a sakinah, mawaddah, warahmah family are all respondents try to carry out religious obligations as well as possible, participate in community activities and recitation, be patient, try to understand each other and understand the condition of the spouse, always be grateful, listen to parental advice, strengthen each other trying to set an example by acting to be a role model for children, especially in religious guidance. By paying attention to the efforts made by a married couple with a speech impairment, they can be grouped into a Sakinah family.